2017
DOI: 10.7556/jaoa.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic Manipulative Treatment to Manage Ophthalmic Conditions

Abstract: Although there is little evidence-based literature regarding osteopathic manipulative treatment for ophthalmic conditions, the general principles and techniques of osteopathic manipulative medicine can be used to manage various ophthalmic pathologic conditions. Additional research to support these treatment options and evaluate the role of OMT as a potential conservative treatment option used by ophthalmologists is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…But several OMT protocols have been described to address mechanical or inflammatory issues around the nasal bones and the upper respiratory tract. 74 , 75 Also, Apoznanski et al showed in a single-case report that one OMT session cured a baby with dacryostenosis, stopping the necessity for antibiotics and avoiding surgical procedure; 76 and Lee-Wong et al showed that self-reported pain, pressure and congestion was significantly improved by OMT in patients with chronic sinusitis. 77 …”
Section: Therapeutic Effects Of Adjunct Omtmentioning
confidence: 99%
“…But several OMT protocols have been described to address mechanical or inflammatory issues around the nasal bones and the upper respiratory tract. 74 , 75 Also, Apoznanski et al showed in a single-case report that one OMT session cured a baby with dacryostenosis, stopping the necessity for antibiotics and avoiding surgical procedure; 76 and Lee-Wong et al showed that self-reported pain, pressure and congestion was significantly improved by OMT in patients with chronic sinusitis. 77 …”
Section: Therapeutic Effects Of Adjunct Omtmentioning
confidence: 99%